2018
DOI: 10.1002/jcsm.12346
|View full text |Cite
|
Sign up to set email alerts
|

Tumour‐derived leukaemia inhibitory factor is a major driver of cancer cachexia and morbidity in C26 tumour‐bearing mice

Abstract: BackgroundCancer cachexia is a metabolic wasting syndrome that is strongly associated with a poor prognosis. The initiating factors causing fat and muscle loss are largely unknown. Previously, we found that leukaemia inhibitory factor (LIF) secreted by C26 colon carcinoma cells was responsible for atrophy in treated myotubes. In the present study, we tested whether C26 tumour‐derived LIF is required for cancer cachexia in mice by knockout of Lif in C26 cells.MethodsA C26 Lif null tumour cell line was made usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 40 publications
11
67
0
Order By: Relevance
“…34 We are encouraged that a simplified rLIF-injected mouse model is appropriate to study cachexia since a recent publication showed that genetic silencing of LIF from the C26 parental tumour line led to an anticipated decrease in systemic levels of IL-6 with suppression of the cachexia phenotype. 35 Therefore, our studies support the premise that cachexia patients have multiple circulating cachexia-inducing factors at any given time explaining why therapeutic interventions targeting a single molecule have been ineffective.…”
Section: Discussionsupporting
confidence: 70%
“…34 We are encouraged that a simplified rLIF-injected mouse model is appropriate to study cachexia since a recent publication showed that genetic silencing of LIF from the C26 parental tumour line led to an anticipated decrease in systemic levels of IL-6 with suppression of the cachexia phenotype. 35 Therefore, our studies support the premise that cachexia patients have multiple circulating cachexia-inducing factors at any given time explaining why therapeutic interventions targeting a single molecule have been ineffective.…”
Section: Discussionsupporting
confidence: 70%
“…It is well-established that C26 cachexia alters the plasma levels of several soluble factors including TNFα, IL-1β and IL-6 which can accelerate the activity of key proteolytic pathways involved in the development of muscle weakness [23,24]. In this study, we confirmed that plasma levels of TNFα, IL-1β and IL-6 are increased in TB-SALINE mice compared to CON-SALINE and CON-SS-31 ( Figure 5).…”
Section: Ss-31 Treatment Does Not Affect Plasma Tnfα Il-1β or Il-6 Lsupporting
confidence: 79%
“…Therefore, the most common in vitro muscle model of cancer cachexia is the treatment of cultured skeletal muscle myotubes with media collected from cultured cancer cells (conditioned media (CM)). The most widely used cachexia-inducing cell lines are the mouse colon adenocarcinoma 26 (C26) and Lewis lung carcinoma (LLC) cells [4], and treatment of C2C12 mouse skeletal muscle myotubes with C26 or LLC CM induces significant atrophy [6][7][8]. Specific proteins identified in these CM that mediate cachexia include interleukin-6 (IL-6), leukemia inhibitory factor (LIF), tumor necrosis factor alpha (TNF-α), and heat shock protein 70 (Hsp70) [6,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used cachexia-inducing cell lines are the mouse colon adenocarcinoma 26 (C26) and Lewis lung carcinoma (LLC) cells [4], and treatment of C2C12 mouse skeletal muscle myotubes with C26 or LLC CM induces significant atrophy [6][7][8]. Specific proteins identified in these CM that mediate cachexia include interleukin-6 (IL-6), leukemia inhibitory factor (LIF), tumor necrosis factor alpha (TNF-α), and heat shock protein 70 (Hsp70) [6,[9][10][11][12]. Further, multiple signaling pathways have been implicated in these models of muscle wasting, including STAT3, ERK1/2, NFkB, FOXO pathways, and, more recently, a TLR/MyD88/XBP1 signaling axis [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation